Analisis Hukum Perlindungan Terhadap Anak Korban Kekerasan Fisik Dalam Rumah Tangga Menurut UU No.35 Tahun 2014 Tentang Perlindungan Anak - Aditia Fernanda Nasution (Universitas Islam Sumatera Utara, 2021)
Writing this journal will describe the backgrounds of children who are often be the victims of physical violence in household and how legal protection for children victims of physical violence in the household is reviewed from UUPA No. 35 of 2014 and what are the legal consequences for the perpetrators of violence against physical violence against children in the household and how to take legal measures to minimize physical violence against children in the household. The problems formulated in the formulation of the problem are How does the rule of Law no. 35 of 2014 provides protection for child victims of physical violence in the household, How is the criminal law policy to the protection of child victims of the crime of physical violence in the household. The approach used is normative juridical method. The normative juridical approach method is used to examine library materials which are primary data. Based on the data obtained, then it is analyzed to draw conclusions after being explained in detail based on available sources. And guarantee the basic rights of every child, provide facilities and infrastructure and protect, nurture and prosper children through the rights and obligations of parents. The criminal law policy regarding the protection of child victims from criminal acts of physical violence in household as referred to in Article 76C, that the perpetrators of physical violence against children shall be sentenced to imprisonment for a maximum of 3 (three) years and 6 (six) years and / or a maximum fine of Rp.72,000,000.00 (seventy two million rupiah). How the non-penal law policy in minimizing the occurrence of child victims of physical violence in the household is more about preventing the occurrence of criminal acts, so that the main objective is to overcome the factors that are conducive to the occurrence of these crimes. This conducive factor focuses on social problems or the conditions that can directly or indirectly cause or foster crime.Keywords : Protection of Child, Victims of Physical Violence at Home, Child protection